Religion and human rights in discourse and practice of cultural relativism and universalism - Марченко, А. (Київський національний університет імені Тараса Шевченка, 2023)
The content and features of the coexistence of universal and local (primarily religious) values and approaches to the problem of human rights are considered; the specifics of the contradictory interaction of religious ideas and attitudes and human rights in the discursive and practical dimensions of cultural relativism and universalism have been studied; the features of the vision of universal and local codes of human rights in Islam, Christianity, in particular Catholicism, in the space of the system of "Asian values" are analyzed; the influence of a dialectical interrelationship between the universality of norms in the private sphere and the religious traditional law on the establishment of the fundamental standards of human rights was examined. It is noted that in the modern world there is a desire of some religions (for example, Islam and Christianity) to connect the idea of universalism and the practice of its assertion with their basic principles, which are given an absolute, comprehensive, infallible nature. In this connection, the topic of religious exclusivity is also relevant, where exclusivism is the belief that my faith is the true faith and other beliefs are wrong. On the other hand, the author points to one of the paradoxes of relativism, which is that it sometimes seeks to become universalism or, rather, absolutism, proposing (and often imposing) a system of its values as the only true. The article emphasizes the necessity to value religious differences, as well as to care for other people, regardless of religion, the need and importance of finding a balance between the universalist understanding of human rights and a diverse, multi-confessional world, combining adherence to certain religious traditions with a commitment to the universality of human rights. As a possible option, an attempt to integrate universal values into the body of the corresponding particular religious and cultural traditions is considered, and, on the other hand, the enrichment of universal human rights standards with relevant unique religious and cultural values.

Розглянуто зміст та особливості співіснування універсальних та локальних (насамперед, релігійних) цінностей і підходів до проблематики прав людини; досліджено специфіку суперечливих взаємин релігійних уявлень і настанов та прав людини в дискурсивних і практичних вимірах культурного релятивізму та універсалізму; проаналізовано особливості бачення універсальних та локальних кодексів прав людини в ісламі, християнстві, зокрема католицизмі, в просторі системи "азійських цінностей". У статті наголошується на необхідності й важливості віднайдення балансу між універсалістським баченням прав людини і різноманітним, поліконфесійним світом, поєднання прихильності до відповідних релігійних традицій з відданістю універсальності прав людини. Як можливий варіант розглядається спроба інтеграції універсальних цінностей в тіло відповідних партикулярних релігійних і культурних традицій, а, з іншого боку, збагачення універсальних стандартів прав людини унікальними релігійно-культурними цінностями.
Релігія і права людини в дискурсах і практиках культурного релятивізму та універсалізму
Keywords: religious values; religious traditions; human rights; cultural relativism; universalism; релігійні цінності; релігійні традиції; права людини; культурний релятивізм; універсалізм